Intensive care experience among intensive care unit survivors - Mohamed Ariffin, Suzilawati; Pinyokham, Nitaya; Tachaudomdach, Chiraporn (Faculty of Nursing. Chiang Mai University, 2018)
Critically ill patients need advanced support to remain alive and prevent serious complications. However, patients may experience either pleasant or unpleasant memories during their stay inICU. Unpleasantexperiences canaffect patientsor lead tolaternegative consequences. Critical care nurses have a pivotal role in identifying traumatic experiences in order to improve care. This study aims to explore the intensive care experiences among ICU survivors. This study was conducted in the general wards of three selected hospitals in Malaysia. Onehundred and forty-two(142) participants agreed totake part inthis study and to answer the Intensive Care Experience Questionnaire (ICEQ) which included additional questions that covered four domains: awareness of surroundings, frightening experiences, recall of experiences, and satisfaction with care. Theresultsof thestudy wereas follows: Halfof thesamples reported ahighawareness of their surroundings. The less aware group reported not being aware of people, place and time. About70% (67.6%)of thesamples reported highlevelsof frighteningexperiences.Pain experienced by the participants came from medical procedures or by the disease process. Only 17.6% of the samples reported being able to recall precisely what happened in the ICU.Participants recalled seeing scary things buthavingenoughsleep intheICU.Theresults showed that43.0% reported beinghighly satisfied withtheir care, and claimed that thestaff waskind and delivered the bestcareto patients.This result indicates thatcriticallyill patients, especiallyintheICU,need strongsupport physicallyand psychologicallyinorder to minimize unpleasant experiences and, later, negative consequences by providing a conducive environment and care with sympathetic concern.